PENGARUH KINERJA KEUANGAN, KEBIJAKAN DIVIDEN DAN KEPEMILIKAN MANAJERIAL TERHADAP MANAJEMEN LABA - Veronika, Elsa; Rahma, Ayumi (Publika Citra Media, 2024)
This research aims to determine the influence of financial performance, dividend policy and managerial ownership on earnings management. The type of research used is a quantitative approach with associative methods. The sampling technique in this research is purposive sampling. The population of this research is 125 non-cyclical consumer sector companies listed on the Indonesia Stock Exchange and after following the sampling criteria, there were 13 companies with a research period of 5 (six) years producing 65 observation data. The data analysis technique used is panel data regression using E-views 12 software. The F test results show that financial performance, dividend policy and managerial ownership simultaneously influence earnings management. The t test results show that financial performance has an effect on earnings management, while dividend policy has no effect on earnings management and managerial ownership has no effect on earnings management.